Nareh Pariaman Embroidery In Fashion As Creative Industry Development - Nofi Rahmanita Nofi Rahmanita; Dini Yanuarmi; Desra Imelda (Institut Seni Indonesia Yogyakarta, 2022)
The aisle in Minangkabau is where the bride (anak daro) sits while waiting for the groom (marapulai) to sit side by side (basandiang) after the marital consent testimony (ijab kabul). In addition to Minangkabau decorations, there are also Chinese and Gujarati motifs. As a creative economic development, the application of aisle embroidery to fashion is related to the creation of economic, social, and environmental added value. The researchers conducted this applied research by innovating the product design through the designing of embroidered fashion. The research employed the participatory observation method, which is also known as active observation. In making a fashion design for aisle embroidery to meet the problems and research objectives, effective steps were taken in several stages, namely: a survey of aisle embroidery craft centers; exploration; analysis, and synthesis; design; and then realization into a fashion work.